Institutional mechanisms to support of the youth entrepreneurship: domestic and foreign experience - Khussainova, Zh.S.; Abauova, G.M.; Bektleyeva, D.Ye.; Zhartay, Zh.M. (BUKETOV BUSINESS REVIEW, 2019)
The article highlights the issue of institutional structure of formation, support, stimulation of youth entrepreneurship in the Republic of Kazakhstan. In particular, the essence of the institutional environment of entrepreneurship is determined and normative legal acts are proposed on the basis of the analysis of scientific sources, as well as the structure of the system of state regulation and stimulation of youth entrepreneurship in the Republic of Kazakhstan is analyzed. Estimates of the youth entrepreneurial climate of the Republic of Kazakhstan as an object of state influence for the formation of favorable conditions for the development of the national economy are given. The authors note the importance of a systematic approach to the formation of the state policy of stimulation and support of youth entrepreneurship. The article reveals the features of management and stimulation, and also defines the main priority directions and target parameters of youth entrepreneurship development in foreign countries.